The rare event: Epistemology and complexity (2016)
Rare events have happened ever since the beginning of this universe. However, they have very recently become the subject of study and a category. This paper studies what rare events are and explores a series of epistemological consequences, thereafter, along with its complexity. The paper introduces a brand new understanding about the sciences of complexity, namely the study of unpredictable phenomena. Unpredictability is the ground, the problem, and the support for complexity as such, something that has never been openly set to the fore in the bibliography about the field.